Niethammerella Eichler, a senior synonym of Kaysius Price & Clayton (Phthiraptera: Amblycera: Menoponidae) - Palma, Ricardo L.; Dalgleish, Robert C.; Price, Roger D. (Zootaxa, 2007)
Eichler (1954: 52) briefly described the new genus Niethammerella to include two morphologically similar species of lice: Machaerilaemus cotingae Carriker, 1949 and M. tityrus (Carriker, 1903), designating the former as the type species. Carriker (1949: 298) had already commented that M. cotingae and M. tityrus “… may warrant the erection of a special genus for their reception.” and that prompted Eichler (1954) to erect Niethammerella. The bird hosts of these two louse species belong to different, though closely related passerine families, that of M. cotingae to the Cotingidae, and M. tityrus to the Tyrannidae.